Narrative Mode in Late Byzantine Painting: Questions it Raises about Sacred Images - Jevtic, Ivana (Actual Problems of Theory and History of Art, 2013)
Narrative imagery is a fundamental element both in the culture and history of fi gural representation. Working from this premise, this paper focuses on the narrative as opposed to iconic-devotional imagery in the Byzantine art. It discusses a selection of compositional methods and features that illustrate the increasing popularity of narrative images and cycles in Late Byzantine mural painting (13th‒15th сс.). It analysis how such techniques and devices infl uenced perception and reception of images and stimulated a stronger interest in their message. Stemming from a research project that investigates the signifi cance of the growing narrative expression in Late Byzantine painting, this paper questions how pictorial discourse was created in such images. In turn, the increased narrative mode in pictorial representations is studied as a sign of deeper transformations in Late Byzantine culture and society: symptoms of a “fi n d’époque”.
Keywords: Late Byzantine Empire; Balkans; 13th to 15th centuries; mural painting; narrative imagery; iconography